DEMOGRAPHIC EVALUATION OF ATTEMPTED SUICIDE BY DRUG OVERDOSE IN ISTANBUL - Karatoprak, CUMALİ; KARATOPRAK, CUMALİ; KARABULUT, Laika; KAYA, Bilgivar; ALTINDAL, Mahmut; UGURLUKISI, Bilal; KILICASLAN, Mehmet Hanifi; ABANONU, Gul Babacan; ÇETİN, GÜVEN; Cetin, GÜVEN; CIKRIKCIOGLU, Mehmet Ali (My University, 2015)
Introduction: In recent years in our country, as well as all over the world, the frequency of attempted suicide by drug overdose is very noticeable. In our study, we aimed to identify general characteristics of patients with drug-attempted suicide, their drug preferences, and the ways in which they obtained the drugs. We conducted an observational study of patients who came to the emergency department with an indication of drug use for attempted suicide during the one-year.